FUT6 Suppresses the Proliferation, Migration, Invasion, and Epithelial–Mesenchymal Transition of Esophageal Carcinoma Cells via the Epidermal Growth Factor Receptor/Extracellular Signal-Regulated Kinase Signaling Pathway - Lao, Jianle; Pang, Yanmin; Chen, Hongming; Tang, Xiqiang; Li, Rizhu; Tong, Danlei; Qiu, Ping; Tang, Qianli (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Esophageal cancer (ESCA) is a high-incidence disease worldwide, of which the 5-year survival rate remains dismal since the cellular basis of ESCA remains largely unclear. Herein, we attempted to examine the manifestation of fucosyltransferase-6 (FUT6) in ESCA and the associated mechanisms. Materials and Methods: The GSE161533 dataset was used to analyze a crucial gene in ESCA. The expression of FUT6 was investigated in normal esophageal epithelial cells and ESCA cell lines. Following FUT6 knockdown or overexpression, cell proliferation, migration, invasion, and levels of epithelial–mesenchymal transition (EMT)-related and epidermal growth factor receptor (EGFR)/extracellular signalregulated kinase (ERK) signaling pathway-related proteins were evaluated using CCK-8, Transwell, and Western blotting with antibodies against EGFR, p-EGFR, E-cadherin, Vimentin, N-cadherin, ERK1/2, and p-ERK1/2), respectively. EGF was administered to stimulate the EGFR/ERK signaling pathway, followed by the assessment of cellular activity. Results: Database analysis revealed that FUT6 was downregulated in the ESCA cells. Our study indicated that FUT6 is suppressed in various ESCA cell lines. Moreover, cell proliferation, invasion, migration, and EMT-related protein levels were conspicuously enhanced or restrained by FUT6 disruption or overexpression. FUT6 overexpression suppressed the malignant activities of the cells when stimulated by EGF, including inhibition of cell growth, movement, invasion, and EMT advancement, as well the reduction the levels of EGFR/ERK pathway proteins. Conclusion: In conclusion, FUT6 can suppress the EGFR/ERK signaling pathway activated by EGF, leading to the potential attenuation of ESCA cell proliferation, invasion, migration, and EMT. Cite this article as: Lao J, Pang Y, Chen H, et al. FUT6 suppresses the proliferation, migration, invasion, and epithelial–mesenchymal transition of esophageal carcinoma cells via the epidermal growth factor receptor/extracellular signal-regulated kinase signaling pathway. Turk J Gastroenterol. 2024;35(9):699-708.